Wild animals in circuses and sport hunting: advancing in the legal protection of animals - Monsalve Mantilla, Milton Duban; Monsalve Mantilla, Yesenia Andrea (DIXI, 2024)
Purpose: The aim of this paper is to describe the legal prohibition of keeping and using wild animals (native or exotic) in circuses; to understand the prohibition of hunting animals for sports or recreational purposes in Colombia; and, finally, to outline some brief conclusions that account for two clear examples in which the best interests in the legal protection of animals are upheld in Colombian law. Methodology: Through a descriptive documentary analysis, the paper investigates the keeping and use of wild animals in circuses, and the impact of sport hunting on the protection of wild animals in Colombia, by reviewing national regulations and case law, and contrasting legislative and judicial decisions. Conclusions: The restriction on the keeping and use of wild animals, both exotic and native, in circus shows, along with the prohibition of recreational hunting, are notable examples of advancements in the legal protection of animals, thanks to the work of the legislator and the judicial decisions by the Constitutional Court of Colombia.
Keywords: Wild animals; sport hunting; circus; legislator; case law